O embate entre o capital e o trabalho: as greves no meio agrário paulista na década de 1980 - Bertero, José Flávio [UNESP] (Universidade Estadual Paulista (Unesp), 1994)
O presente texto consiste num estudo das greves dos trabalhadores rurais no Estado de São Paulo, na década de 1980 Tais greves são vistas como expressões das contradições sociais reinantes no campo, decorrentes da sua industrialização. Daí a similitude entre as greves com que se defronta e as greves operárias.

This article presents a study of strikes of rural workers in São Paulo State in the 80's. These strikes are seen as expressions of present social contradictions in the rural areas due to industrialization. The similitude between the rural strikes and the workmen strikes will be discussed based on these assumptions.
The argument between the capital and work: the rural strikes in the interior of São Paulo in the 80's
Keywords: Trabalho; capital; exploração; conflitos; greves; lutas de classe